Feasibility Analysis of Biodiesel Plant Development Model in Aceh Province - Khalsiah Khalsiah; Rozanna Dewi; Yesy Afrillia; Gilang Ramadhan; Muzaffar Rigayatsyah (LPPM Universitas Malikussaleh, 2022)
Agricultural development that is generally carried out in rural areas is very important for a country because it has a very broad role such as producing food for the people, providing a source of income and employment for rural residents, providing a source of raw materials for the industrial sector, encouraging national and regional economic growth and preserving the environment technological developments allow agriculture to have a new role as a source of energy for life in the form of biofuels. Dependence on energy sourced from fossil fuels, especially petroleum, is getting higher and has encouraged Indonesia to develop biofuels such as biodiesel given the availability of abundant raw materials in the form of palm oil. Currently, Indonesia is the largest producer of palm oil in the world. so that the community has an alternative choice of fuel to be used and dependence on fossil fuels can be reduced and improve the economic welfare of the community, especially oil palm farmers. The study covers the aggregate area of Aceh province and commodities restricted to biodiesel derived from palm oil as the leading raw material for biodiesel in Indonesia. The feasibility level of the region (west or east) of Aceh province that has the potential for biodiesel plant development is projected through a model and economic analysis. PT Perkebunan Lembah Bhakti (Astra Agro Lestari Tbk) in Aceh Singkil regency, Aceh province built 1,000 hectares of plasma oil palm plantations in an effort to increase the productivity of the company's management and improve the economy of the local community. PT Ika Bina Agro Wisesa in the Guha Uleu area, Kuta Makmur District, North Aceh Regencyaccommodates around 700 tons of palm oil bunch owned by local farmers.